CHANGE OF LANGUAGE DEVELOPMENT WITH FINGER PUPPETS STIMULATION IN CHILDREN'S PRESCHOOL - Rukanah, Rukanah; Farihatin, Yuyun; Fitriani, Yunita Dyah (Journal of Vocational Nursing, 2022)
Introduction: The study is based on a lack of children's language skills to repeat the contents of the previous story”evidence of the speaking ability of most children not being good enough. An easy-to-use verbal skill stimulation tool is the finger puppet. Stimulation finger puppet effective with storytelling method. This study aims to analyze the effectiveness of finger puppet stimulation on the language development of preschool children. Methods: This study used to pretest and posttest control group design. The sampling technique was simple random sampling, with a sample of 66 respondents (33 intervention, 33 control). The research instrument by observation used a checklist. The bivariate analysis uses the Wilcoxon and Mann-Whitney tests with a significance level α<0,05. Results: The Wilcoxon test showed finger puppet stimulation effectively improved children's language development in the intervention group (p=0,000). The Mann-Whitney test shows a difference between children's language development in the intervention group and the control group (p=0,000). Conclusions: The development of children's language will be better stimulation often because, with simulation, children will record the language known and practice when communicating with other people.